Оптимізація структури капіталу та її вплив на фінансовий стан підприємства - Петряєва, З. Ф. (НТУ "ХПІ", 2014)
В рамках дослідження автором узагальнено основні чинники, які впливають на структуру капіталу підприємств. Запропоновано рекомендації, спрямовані на вдосконалення аналізу структури капіталу підприємства та прогнозування темпів зростання чистого прибутку. Побудовано модель залежності показника темпів зростання чистого прибутку від факторів, які обумовлюють показник. Розкрито економічний сенс розробленої моделі і обґрунтовано можливість її використання для прогнозування темпів зростання чистого прибутку. Запропоновано впровадження у сферу управління підприємством сучасних комп'ютерних технологій, використання математичних методів у процесі вирішення економічних завдань.

Within the framework of the research the author generalises basic factors which influence the structure of enterprises capital. The structure of financial resources of enterprises is analysed. Recommendations directed on improving the analysis of on enterprise capital structure and prognostication of net income rates of growth are offered. The model of dependence of an index of net income growth rates of on the factors, stipulating an index is developed: of coefficient of financial risk, coefficient of financial dependence, coefficient of turnover of the total capital and specific gravity of account payable in the total capital. The economic essence of the developed model is revealed and the possibilities of its application to prognostication of net income growth rates of are justified. The enterprise the implementation of modern computer technologies into the sphere of management, as well as the use of mathematical methods in the process of solving economic tasks are offered.
Optimization of capital structure and its influence on the financial position of enterprises
Keywords: ринкові відносини; капітал; використання капіталу; позиковий капітал; власний капітал; структура капіталу; фінансовий стан; eguity and loan capital; capital structure; financial position; progress trends; computer technologies